2015
DOI: 10.1194/jlr.m052977
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic insulin resistance in ob/ob mice involves increases in ceramide, aPKC activity, and selective impairment of Akt-dependent FoxO1 phosphorylation

Abstract: Insulin resistance with resultant hyperinsulinemia refl ects an impairment in insulin-regulated glucose homeostasis, and is a key pathogenic element in obesity, metabolic syndrome features, and type 2 diabetes mellitus (T2DM). In this regard, primary impairments in insulin-stimulated glucose transport in muscle owing to muscle-specifi c knockout of the insulin receptor, the Glut4 glucose transporter, or atypical protein kinase C (aPKC), PKC-can induce insulin resistance and development of obesity, metabolic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 29 publications
4
99
0
Order By: Relevance
“…We subsequently injected both the transgenic and WT mice with either PBS or 2-acetyl-1,3-cyclopentanedione (ACPD), a known PKCζ inhibitor demonstrated in previous studies to effectively reduce PKCζ activity (Sajan et al, 2014b), and compared the results with WT and transgenic mice fed a doxycycline diet. For the Alb-AC cohort, we found that injection of ACPD for one month in WT and Alb-AC mice resulted in the same improvements in insulin sensitivity and reduction in hepatic lipid accumulation as Alb-AC mice fed a HFD-dox diet for the same time (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently injected both the transgenic and WT mice with either PBS or 2-acetyl-1,3-cyclopentanedione (ACPD), a known PKCζ inhibitor demonstrated in previous studies to effectively reduce PKCζ activity (Sajan et al, 2014b), and compared the results with WT and transgenic mice fed a doxycycline diet. For the Alb-AC cohort, we found that injection of ACPD for one month in WT and Alb-AC mice resulted in the same improvements in insulin sensitivity and reduction in hepatic lipid accumulation as Alb-AC mice fed a HFD-dox diet for the same time (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phosphorylation site alters the affinity for Akt to 3,4,5-trisphosphate, thus interfering with Akt translocation to plasma membrane microdomains where it is activated (Fox et al, 2007). A recent report by the Farese group suggests that aberrant activation of atypical PKC, is evident in livers of Lep ob/ob mice and is essential for impairments in Akt mediated signaling to FoxO1; this is rescued in vivo by pharmacological inhibition of atypical PKCs (Sajan et al, 2014b). PKCζ has also attracted attention for its role in lipid homeostasis, particularly as a mediator of SREBP-1c driven lipogenesis (Sajan et al, 2004; Sajan et al, 2009; Taniguchi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in mouse diet-induced obesity (DIO), caloric excesses provoke initial increases in hepatic gluconeogenic enzymes that lead to systemic insulin resistance and liverdependent decreases in insulin signaling in muscle (3, 4). Assuming that dietary excesses are also important in human obesity, the startup of insulin resistance therein is likely to involve alterations in hepatic factors that promote gluconeogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in liver, dietary excesses of fat (3) or carbohydrate (4) in mouse DIO lead to increases in ceramide, which, perhaps with other lipids [e.g., phosphatidic acid (PA)], directly activates aPKC. Combined activation of aPKC by ceramide and hyperinsulinemia-derived PIP 3 causes excessive aPKC accumulation on scaffolding protein, WD40/ProF, and displacement of activated Akt from this platform, where Akt otherwise phosphorylates/inhibits FoxO1 (3, 4, 2123).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic gluconeogenic and glycolytic pathways are predominantly regulated by the transcription factor forkhead box O1 (FoxO1), one of the major intracellular targets of insulin, through inhibition of transcriptional activation of relevant key enzymes [16,17]. However, Akt-dependent FoxO1 phosphorylation is selectively impaired in ob/ob mice with hepatic insulin resistance [18]. Furthermore, overexpression of FoxO1 facilitates hepatic glucose production, indicating a critical role of FoxO1 in the regulation of glucose homeostasis [19].…”
Section: Introductionmentioning
confidence: 99%